Iddah for Men: A Comparative Study of Wahbah Zuhaili and Faqihudin Abdul Kodir - Khairuddin, Khairuddin (Abdurrauf Journal of Islamic Studies, 2024)
The waiting period or better known as iddah applies to women after divorce. Iddah divorce lives three months and ten days, divorce dies four months and ten days, conceives until childbirth, divorce during menstruation three quru'. This study aims to analyze the opinions of Wahbah Zuhaili and Faqihuddin Abdul Kodir on the implementation of iddah for men. In this qualitative research, analytical descriptive-comparative studies were conducted. The results revealed that Wahbah Zuhaili said for men it applies to iddah like a woman's iddah if married to his ex-wife's mahram. Meanwhile, Faqihuddin Abdul Kodir said that men have iddah like women's iddah after divorce because, iddah not only aims to see the emptiness of the uterus, but also looks at social, psychological, and gender equality aspects. Masa menanti atau lebih dikenal dengan sebutan iddah berlaku kaum wanita pasca perceraian. Iddah cerai hidup tiga bulan sepuluh hari, cerai mati empat bulan sepuluh hari, mengandung sampai melahirkan, cerai pada masa haid tiga quru’. Penelitian ini bertujuan untuk menganalisis pendapat Wahbah Zuhaili dan Faqihuddin Abdul Kodir tentang pemberlakuan iddah bagi laki-laki. Dalam penelitian kualitatif ini dilakukan studi deskriptif-komparatif analitis. Hasil penelitian mengungkap bahwa Wahbah Zuhaili mengatakan bagi laki-laki berlaku bagi iddah seperti iddah perempuan jika menikah dengan mahram mantan istrinya. Sedangkan Faqihuddin Abdul Kodir mengatakan bahwa laki-laki memiliki iddah seperti iddah perempuan pasca perceraian karena, iddah bukan saja bertujuan untuk melihat kosongnya rahim saja, akan tetapi juga memandang segi sosial, psikologis, dan kesetaraan gender